2010
DOI: 10.1007/s00125-009-1650-y
|View full text |Cite
|
Sign up to set email alerts
|

Independent effects of weight gain and fetal programming on metabolic complications in adults born small for gestational age

Abstract: Aims/hypothesis Insulin resistance (IR) and the metabolic syndrome (MS) have been reported in adults as a consequence of being born small for gestational age (SGA). The process seems to be initiated early in life; however, little is known about the progression of MS and IR in young adults. We hypothesised that being born SGA would promote a greater progression over time of IR and MS, reflecting not only the gain in weight and fat mass but also the extension of the fetal programming process. Methods Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 30 publications
4
50
1
2
Order By: Relevance
“…30,31 Some studies have found that the effects of birthweight on coronary heart disease are limited to those with high adult BMI 15 or that fetal growth and adult BMI or weight gain interact. 32,33 We also found a relationship between BMI and effects of fetal growth. Many children born small remained small, putting them at lower risk for several metabolic syndrome risk factors.…”
Section: Discussionsupporting
confidence: 55%
“…30,31 Some studies have found that the effects of birthweight on coronary heart disease are limited to those with high adult BMI 15 or that fetal growth and adult BMI or weight gain interact. 32,33 We also found a relationship between BMI and effects of fetal growth. Many children born small remained small, putting them at lower risk for several metabolic syndrome risk factors.…”
Section: Discussionsupporting
confidence: 55%
“…Insulin resistance plays a central role in the metabolic syndrome and adults born SGA are more insulin-resistant than controls [2,3]. Insulin sensitivity is already reduced in SGA born children, especially in children with catch-up growth [6,7,9,11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Besides lifestyle and obesity, fetal and early postnatal growth are determinants of the metabolic syndrome. Both term small-for-gestational-age (SGA) infants and preterm born infants have an increased prevalence of several components of the metabolic syndrome in later life, not only in adulthood [1,2,3,4,5], but already in childhood [6,7,8,9,10,11,12,13]. Studies in very-low-birth-weight (VLBW) infants show increased blood pressure and insulin resistance in adulthood [14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The adaptation of the fetus to conditions of undernutrition in utero involves a gene-environment interaction called fetal programming [1,2] which may modify gene expression permanently. However, the mechanisms underlying this relationship are far from understood, and the relative contributions of intrauterine growth retardation and postnatal growth rates have been controversial.…”
Section: Introductionmentioning
confidence: 99%